Controlling exposure to diesel emissions in underground mines - Bugarski, Aleksandar D. (Society for Mining, Metallurgy, and Exploration, Inc., 2012)
The use of diesel-powered equipment in underground mining operations provides many benefits to the industry. It also presents many challenges to the health and safety of workers as it is a significant source of submicrometer aerosols and noxious gases. This book was developed to assist the coal and metal/nonmetal underground mining industries in their efforts to reduce the exposure of workers to aerosols and gases from diesel-powered equipment. It includes information collected by researchers at the National Institute for Occupational Safety and Health/ Office of Mine Safety and Health Rese.